French food safety labeling system and enlightenment - JIANG Ding; CHEN Wen-hua (Shipin yu jixie, 2023)
The elements of the French food safety labeling system include specialized management organizations, diversified use objects and diversified identification types. Its text characteristics are reflected in the establishment of a diversified system and standard system, the construction of the cooperation mechanism between the government and market entities, and the attention to the standardized construction of special food safety labeling.In this regard, China's food safety labeling system can be optimized and constructed from the dimensions of improving the diversified food labeling standard system based on Article 71 of the Food Safety Law, building a self-regulatory management standard system with supermarkets and agricultural products markets as the core, and adding a special labeling standard system and mechanism for special food safety.